Pengaruh Kepercayaan, Kenyamanan Dan Promosi Terhadap Keputusan Penggunaan Aplikasi Online Food Delivery (Ofd) : (Studi Kasus: Pengguna Gofood Dan Maxim Food Di Kota Ambon) - Aprillianti Jeane Matulessy; Arthur Sitaniapessy; Marie Ch Tahalele (Journal Of Business, Finance, and Economics (JBFE), 2025)
This study aims to analyze the influence of trust, convenience, and promotion on the decision to use online food delivery applications among GoFood and Maxim Food users in Ambon City. The research method uses a quantitative approach with purposive sampling technique involving 120 respondents. Data were collected through online questionnaires using a Likert scale and analyzed using multiple linear regression with SPSS version 25 software. The results show that trust has a significant positive influence on usage decisions with a t-value of 9.807, convenience has a significant positive influence with a t-value of 6.495, and promotion has the most dominant significant positive influence with a t-value of 18.386. The three variables explain 89.6% of the variation in usage decisions. Although all three variables have significant effects, the levels of trust, convenience, and promotion are still in poor categories. The research findings imply that service providers need to improve transaction transparency, simplify application interfaces, and optimize promotional strategies to increase competitiveness in the online food delivery service industry.